ReL: A Generic Refactoring Language for Specification and Execution - Ruhroth, Thomas; Wehrheim, Heike; Ziegert, Steffen (37th EUROMICRO Conference on Software Engineering and Advanced Applications, SEAA 2011, Oulu, Finland, August 30 - September 2, 2011)

Verifying Linearisability with Potential Linearisation Points - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (FM 2011: Formal Methods - 17th International Symposium on Formal Methods, Limerick, Ireland, June 20-24, 2011. Proceedings)

Sound and Complete Abstract Graph Transformation - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (Formal Methods, Foundations and Applications - 14th Brazilian Symposium, SBMF 2011, São Paulo, Brazil, September 26-30, 2011, Revised Selected Papers)

A CSP Account of Event-B Refinement - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Proceedings 15th International Refinement Workshop, Refine@FM 2011, Limerick, Ireland, 20th June 2011.)

Selected papers on Integrated Formal Methods (iFM09) - Leuschel, Michael; Wehrheim, Heike (Science of Computer Programming)

Reputation-based Reliability Prediction of Service Compositions - Besova, Galina; Wehrheim, Heike; Wagner, Annika (Electronic Notes in Theoretical Computer Science)
Today, the concept of service oriented architectures provides a way of building integrated solutions out of existing services. To this end, services from different providers are composed using advanced orchestration and choreography techniques. However, while this principle allows for greater flexibility at a smaller cost, the use of third party services also includes a risk: Deployed services might not work as claimed by their providers. In this paper, we propose a technique for analyzing the expected reliability of service compositions based on ratings given by (previous) service users. Every service thereby comes with a reputation, and the analysis computes an overall reliability of a service composition from the reputations of its constituent services. The proposed model-driven approach proceeds by translating statechart models of service compositions into input for a probabilistic model checker (PRISM) using state-of-the-art model transformations techniques. The approach has been implemented as an Eclipse plug-in and is fully compliant with UML.

Function Specification Inference Using Craig Interpolation - Schremmer, Alexander

A CSP Approach to Control in Event-B - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Integrated Formal Methods - 8th International Conference, IFM 2010, Nancy, France, October 11-14, 2010. Proceedings)

{SLAB:} A Certifying Model Checker for Infinite-State Concurrent Systems - Dräger, Klaus; Kupriyanov, Andrey; Finkbeiner, Bernd; Wehrheim, Heike (Tools and Algorithms for the Construction and Analysis of Systems, 16th International Conference, TACAS 2010, Held as Part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2010, Paphos, Cyprus, March 20-28, 2010. Proceedings)

Towards A Shape Analysis for Graph Transformation Systems - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (CoRR)

Model transformations across views - Derrick, John; Wehrheim, Heike (Sci. Comput. Program.)

Model-Driven Development with Mechatronic UML - Schäfer, Wilhelm; Wehrheim, Heike (Graph Transformations and Model-Driven Engineering - Essays Dedicated to Manfred Nagl on the Occasion of his 65th Birthday)

On Symmetries and Spotlights - Verifying Parameterised Systems - Timm, Nils; Wehrheim, Heike (Formal Methods and Software Engineering - 12th International Conference on Formal Engineering Methods, ICFEM 2010, Shanghai, China, November 17-19, 2010. Proceedings)

Showing Full Semantics Preservation in Model Transformation - A Comparison of Techniques - Hülsbusch, Mathias; König, Barbara; Rensink, Arend; Semenyak, Maria; Soltenborn, Christian; Wehrheim, Heike (Integrated Formal Methods - 8th International Conference, IFM 2010, Nancy, France, October 11-14, 2010. Proceedings)

Compositional CSP Traces Refinement Checking - Wehrheim, Heike; Wonisch, Daniel (Electr. Notes Theor. Comput. Sci.)

Static Class Elements for Object-Z - Ruhroth, Thomas; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Measure, Diagnose, Refactor: A Formal Quality Cycle for Software Models - Ruhroth, Thomas; Voigt, Hendrik; Wehrheim, Heike (35th Euromicro Conference on Software Engineering and Advanced Applications, SEAA 2009, Patras, Greece, August 27-29, 2009, Proceedings)

Integrated Formal Methods, 7th International Conference, IFM 2009, Düsseldorf, Germany, February 16-19, 2009. Proceedings

Refinement in the Presence of Unknowns - Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Alloy as a Refactoring Checker? - Estler, H.{-}Christian; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)